(untitled) (Journal of Science and Technology, 2016)
Review of factors influencing wood durability shows although density varies depending on trunk position, its role appears controversial for many timber species. Thus, for the first time, the influence of density on the durability of three Ghanaian timbers (Nauclea diderrichii (de Wild.) Merr., Nesogordonia papaverifera (A. Chev.) R. Capuron and Corynanthe pachyceras Welw.) [a Lesser-Utilized-Species (LUS)] is investigated, particularly for tropical species. Stake density was determined using its corrected oven-dry weight and conditioned volume. Extracted density was based on its density and total extractive content determined using 1:2 ethanol-toluene. Mean weight losses (%) for stakes from inner and outer heartwoods (IHW and OHW respectively) of each timber and the middle sapwood (MSW) of C. pachyceras, after exposure to Coriolus versicolor (Linnaeus) Quelet. (a white-rot decay-fungus), were determined and correlated with their densities (unextracted and extracted). Mean densities for N. diderrichii, N. papaverifera and C. pachyceras range between 660-720, 640-700 and 720-820kgm3 respectively for their corresponding IHWs and OHWs, while MSW of C. pachyceras measures 655-794kgm3. Total extractive contents for the heartwoods of the three species range between 13.29-13.96, 10.18-10.65 and 11.03-14.19% respectively, while that of MSW of C. pachyceras is 9.68%. Relationship between densities at the stem positions and their weight losses resulting from decay by C. versicolor shows weak correlations: R2 = 0.0095, 0.0103 and 0.1251 for N. diderrichii, N. papaverifera and C. pachyceras respectively for their unextracted densities, and R2 = 0.0109, 0.015 and 0.1245 respectively for their extracted densities. Thus, the current study shows density alone has little influence on the decay resistance of the three tropical timbers against bio-deteriogens (e.g. C. versicolor) and that other factors such as extractives play much role in wood durability.